Higher CSF sTREM2 and microglia activation are associated with slower rates of beta‐amyloid accumulation - Michael Ewers; Gloria Biechele; Marc Suárez‐Calvet; Christian Sacher; Tanja Blume; Estrella Morenas‐Rodriguez; Yuetiva Deming; Laura Piccio; Carlos Cruchaga; Gernot Kleinberger; Leslie Shaw; John Q Trojanowski; et al. (EMBO Molecular Medicine)
Abstract Microglia activation is the brain's major immune response to amyloid plaques in Alzheimer's disease (AD). Both cerebrospinal fluid (CSF) levels of soluble TREM2 (sTREM2), a biomarker of microglia activation, and microglia PET are increased in AD; however, whether an increase in these biomarkers is associated with reduced amyloid‐beta (Aβ) accumulation remains unclear. To address this question, we pursued a two‐pronged translational approach. Firstly, in non‐demented and demented individuals, we tested CSF sTREM2 at baseline to predict (i) amyloid PET changes over ∼2 years and (ii) tau PET cross‐sectionally assessed in a subset of patients. We found higher CSF sTREM2 associated with attenuated amyloid PET increase and lower tau PET. Secondly, in the AppNL‐G-F mouse model of amyloidosis, we studied baseline 18F‐GE180 microglia PET and longitudinal amyloid PET to test the microglia vs. Aβ association, without any confounding co‐pathologies often present in AD patients. Higher microglia PET at age 5 months was associated with a slower amyloid PET increase between ages 5‐to‐10 months. In conclusion, higher microglia activation as determined by CSF sTREM2 or microglia PET shows protective effects on subsequent amyloid accumulation.